Persistent colonization of non-lymphoid tissue-resident macrophages by Stenotrophomonas maltophilia. (20th October 2019) - Takahashi, Ichiro; Hosomi, Koji; Nagatake, Takahiro; Toubou, Hirokazu; Yamamoto, Daiki; Hayashi, Ikue; Kurashima, Yosuke; Sato, Shintaro; Shibata, Naoko; Goto, Yoshiyuki; Maruyama, Fumito; Nakagawa, Ichiro; et al.
Abstract : S. maltophilia colonize and regulate colonic macrophages Abstract: Accumulating evidence has revealed that lymphoid tissue-resident commensal bacteria (e.g. Alcaligenes spp.) survive within dendritic cells. We extended our previous study by investigating microbes that persistently colonize colonic macrophages. 16S rRNA-based metagenome analysis using DNA purified from murine colonic macrophages revealed the presence of Stenotrophomonas maltophilia . The in situ intracellular colonization by S. maltophilia was recapitulated in vitro by using bone marrow-derived macrophages (BMDMs). Co-culture of BMDMs with clinically isolated S. maltophilia led to increased mitochondrial respiration and robust IL-10 production. We further identified a 25-kDa protein encoded by the gene assigned as smlt2713 (recently renamed as SMLT_RS12935) and secreted by S. maltophilia as the factor responsible for enhanced IL-10 production by BMDMs. IL-10 production is critical for maintenance of the symbiotic condition, because intracellular colonization by S. maltophilia was impaired in IL-10-deficient BMDMs, and smlt2713 -deficient S. maltophilia failed to persistently colonize IL-10-competent BMDMs. These findings indicate a novel commensal network between colonic macrophages and S. maltophilia that is mediated by IL-10 and smlt2713 .